QCD corrections to the electroproduction of hadrons with high pT - Daleo, A. (2005)
We compute the order αs2 corrections to the one particle inclusive electroproduction cross section of hadrons with non vanishing transverse momentum. We compare our results with H1 data on forward production of π0, and conclude that the data is well described by the DGLAP approach. within the theoretical uncertainties. © 2005 American Institute of Physics.